Who Wrote the Trisvabhāvanirdeśa? Reflections on an Enigmatic Text and Its Place in the History of Buddhist Philosophy. - Kapstein, Matthew T. (Journal of Indian Philosophy, 2018)
In recent decades, scholars of Buddhist philosophy have frequently treated the Trisvabhāvanirdeśa (TSN), or "Teaching of the Three Natures," attributed to Vasubandhu, as an authentic and authoritative representation of that celebrated thinker's mature work within the Yogācāra tradition. However, serious questions may be posed concerning the status and authority of the TSN within Yogācāra, its true authorship, and the relation of its contents to trends in early Yogācāra thought. In the present article, we review the actual state of our knowledge of the TSN's possible origins, considering, too, the implications this may have for contemporary treatments thereof.